(untitled) (Indonesian Journal of Cultural and Community Development, 2024)
Background: The rise of social media has transformed marketing strategies, particularly in e-commerce. Specific Background: This study examines how affiliate marketers on TikTok enhance consumer engagement and purchasing decisions. Knowledge Gap: Limited understanding exists regarding the specific communication strategies that TikTok affiliates use to influence consumer perceptions. Aims: The research analyzes the communication concepts employed by a TikTok affiliate account to attract consumers. Results: Findings reveal that product reviews by creators serve as credible sources of information, reducing consumer uncertainty and building trust. Novelty: This study offers unique insights into the dynamics of affiliate marketing on TikTok, highlighting benefits for both creators and store owners through authentic promotions. Implications: The research emphasizes the importance of effective communication in affiliate marketing, suggesting that these strategies not only enhance consumer trust but also facilitate organic campaigns that expand market reach with minimal advertising costs. Highlights : • Credible Information: Product reviews by creators help reduce consumer uncertainty. • Trust Building: Honest evaluations foster stronger relationships between creators and audiences. • Organic Reach: Effective communication strategies enhance marketing campaigns without high advertising costs. Keywords: TikTok, Affiliate, Marketing, Consumer, Trust